Carbon Emission Disclosure, Green Intellectual Capital Terhadap Kinerja - Eny Maryanti; Sarwenda Biduri; Herlinda Maya Kumala Sari (Politeknik Ganesha Medan, 2025)
This study investigates the impact of CED and Green Intellectual Capital (GIC) on financial performance and firm value, which are crucial metrics for assessing a company's sustainability and market reputation. Despite the growing emphasis on environmental responsibility, the adoption of CED and GIC remains inconsistent, particularly in emerging markets like Indonesia. Previous research has shown mixed results on the relationship between these factors and financial outcomes. This study aims to clarify the effects of CED and GIC on financial performance and firm value. The findings reveal that CED positively impacts both financial performance and firm value, while GIC significantly influences firm value but not financial performance. This study uniquely integrates CED and GIC in the context of Indonesian firms. The results underscore the importance of environmental disclosures and intellectual capital in enhancing firm value, offering strategic insights for policymakers and practitioners.